2021
DOI: 10.4103/ijo.ijo_1464_20
|View full text |Cite
|
Sign up to set email alerts
|

Modified inexpensive needle for suprachoroidal triamcinolone acetonide injections in pseudophakic cystoid macular edema

Abstract: Pseudophakic cystoid macular edema (PCME) is one of the leading causes of reduced vision, after cataract surgery. Topical steroids and nonsteroidal anti-inflammatory drops are frequently used in the management; however, intravitreal injections may be required for chronic cases. Suprachoroidal injection of preservative free Triamcinolone acetonide is a recent addition to the therapeutic armamentarium of ophthalmologists for treatment of cystoid macular edema of varied etiology. Though the drug is commercially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…14 Furthermore, Oli and Waikar used a similar technique to the present study for suprachoroidal injection of triamcinolone acetonide using a 26-G needle and sleeve of intracath with marked BCVA improvement and CMT reduction with no elevation of IOP. 15 The present study reported a significant reduction of the CMT and a significant improvement of BCVA after 12 months of SCTA confirming good anatomical and functional results of SCTA in resistant DME cases, this is quite similar to a recent study (HULK Trial; N=20) that assessed the efficacy of SCTA in naïve and previously treated DME patients. In the HULK trial, the mean number of injections prior to SCTA was 21.6.…”
supporting
confidence: 91%
“…14 Furthermore, Oli and Waikar used a similar technique to the present study for suprachoroidal injection of triamcinolone acetonide using a 26-G needle and sleeve of intracath with marked BCVA improvement and CMT reduction with no elevation of IOP. 15 The present study reported a significant reduction of the CMT and a significant improvement of BCVA after 12 months of SCTA confirming good anatomical and functional results of SCTA in resistant DME cases, this is quite similar to a recent study (HULK Trial; N=20) that assessed the efficacy of SCTA in naïve and previously treated DME patients. In the HULK trial, the mean number of injections prior to SCTA was 21.6.…”
supporting
confidence: 91%
“…Localized subconjunctival hemorrhage was noted in one eye (16.6%), no inadvertent intravitreal injection had been occurred, and only one patient (16.6%) reported a localized pain immediately after injection which was controlled by systemic pain killer, our results are consistent with recent publications used the same injection technique. 21,22 Nazari et al reviewed the OCT of 12 eyes (6 patients) with acute VKH and observed that the height of the subretinal fluid in the OCT was correlated with visual acuity, the height of the subretinal fluid in the initial presentation did not correlate with resolution time and final visual acuity. 23 These results are similar to our study, but we find that SCTA helped our patients to gain rapid visual improvement, reduced the dosage of systemic steroids and earlier tapering of steroids as all patients tapered systemic steroids within 3 months from recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Localized subconjunctival hemorrhage was noted in one eye (16.6%), no inadvertent intravitreal injection had been occurred, and only one patient (16.6%) reported a localized pain immediately after injection which was controlled by systemic pain killer, our results are consistent with recent publications used the same injection technique. 21,22…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study showed that SCTA injection using a microneedle led to significant CMT reduction and BCVA improvement without an increase in IOP (Oli and Waikar, 2021). Another previous study on the evaluation of SCTA reported that mean CMT decreased from 636.6±200.10µm to 302.67 ± 66.94 µm after three months of the treatment.…”
Section: Discussionmentioning
confidence: 81%
“…Previously DME was mainly treated by lasers (Blinder et al, 2017), but these days anti-vascular endothelial growth factors(anti-VEGF agents) are increasingly being used for its treatment. Despite their increasing use, some patients do not respond to this therapy (Schmidt-Erfurth et al, 2017). Triamcinolone acetonide (TA), a systemic corticosteroid, is used to treat different inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%